2014
DOI: 10.1016/j.otsr.2013.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Cryotherapy with dynamic intermittent compression for analgesia after anterior cruciate ligament reconstruction. Preliminary study

Abstract: Level III, case-control study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 19 publications
1
32
0
3
Order By: Relevance
“…** indicates p < 0.01 and *** indicates p < 0.001 administered post-surgery by reducing the formation of oedema [5]. In particular, a study by Murgier and Cassier (2014) showed that dynamic compression together with cooling was more effective in reducing postoperative pain than static compression with cooling [19]. The gate control theory of pain explains how non-painful sensory inputs could inhibit pain sensations from being transmitted to the brain [16].…”
Section: Discussionmentioning
confidence: 99%
“…** indicates p < 0.01 and *** indicates p < 0.001 administered post-surgery by reducing the formation of oedema [5]. In particular, a study by Murgier and Cassier (2014) showed that dynamic compression together with cooling was more effective in reducing postoperative pain than static compression with cooling [19]. The gate control theory of pain explains how non-painful sensory inputs could inhibit pain sensations from being transmitted to the brain [16].…”
Section: Discussionmentioning
confidence: 99%
“…CDIC has been used in the sports medicine setting to improve recovery and to treat ligament and bone injuries [8,16]. It has been shown that CDIC improves postoperative recovery by stimulating the tissue repair process [17].…”
Section: Discussionmentioning
confidence: 99%
“…These devices provide a dry cold temperature and maintain a consistent temperature for an extended period of time [4,7]. Although the benefits of these systems were demonstrated in primary TKA [7] and anterior cruciate ligament reconstruction [8], we did not find any published studies evaluating the effect of CDIC in patients undergoing rTKA.…”
mentioning
confidence: 89%
“…Th e general tendency is to prefer the CKCE due to the fact that they are predominantly focused on increasing muscle strengh on the quadriceps, and improving coordination. Th erefor CKCE are considered to be safer because they do not increase the tensile strain on the ACL and so, reduce the risk of tibial displacement, while using open chain kinetic exercises for ACL rehabilitation might increase the anterior shear of the knee 21,22 . Tagesson et al (2008) express signifi cant results for open chain kinetic exercises only in terms of muscle strengh on the quadriceps compared to CKCE, while functional outcome is similar in both cases 23 .…”
Section: Resultsmentioning
confidence: 99%
“…No diff erences were observed between low and high intensity plyometric exercises by some authors, (Chmielewski et al 2016), both type of exercises inducing favorable eff ects on knee function and psychosocial factor 41 . Stationary bike could begin after 4 weeks with gradual rapy combined with dynamic intermitent compression which has been proposed as an alternative to permanent static compression, that could provide better tissue oxygenation, and better facilitate soft tissue exchanges, on the same time decreasing the risk of skin necrosis associated with static cryotherapy 48 . Despite the widespread use of cryotherapy, there are still diff erences of opinion in the literature concerning the eff ectiveness of its various application methods and the quantifi cation of variables such as frequency, duration and best time for use.…”
Section: Introductionmentioning
confidence: 99%